“Kampung Preman” Community Empowerment In Communicative Action Theoretical Study (A Case Study in Yogyakarta Indonesia) - setyowati, yuli; muktiyo, widodo; wijaya, mahendra; pinta, sarah rum handayani (Advances in Social Sciences Research Journal, 2017)
Abstract The establishment of communicative community in the context of “Kampung Preman” community can be seen from the community’s communicative action, formerly living in violent and conflicting condition in contradiction with communicative community typology characterized with equal and harmonious relation. Through its communicative action, people (community) will change over time toward the guyub rukun communicative community. Therefore, this study on community empowerment viewed from communicative action is interesting as the history and characteristics of “Kampung Preman” community is very unique. This study aimed to analyze the process of empowering “kampong preman’ community viewed from communicative action theory. This research was conducted descriptive qualitatively in Yogyakarta using case study. The data was collected using in-depth interview, observation, and documentation techniques. Data validation was carried out using source and method triangulations. Data analysis was conducted using an interactive model of analysis. The result of research showed that community’s communicative action built on four claims according to Habermas’ communicative action theory in empowerment process reveals the community’s ability of driving them toward a life condition based on the mutually approved values and norms to control their own behavior or called self-regulation. Social groups function as public spaces for the community of express, thereby growing emancipation and solidarity among the communities. Keywords: empowerment, community, action, communication